Challenges experienced by healthcare workers when rendering services at a district hospital in the Limpopo Province, South Africa - Nchabeleng, Mpelegeng Trudy (My University, 2022)
Background: Healthcare workers (HCWs) are faced with several challenges when rendering services in hospitals. These challenges usually lead them to render low quality healthcare service to patients. Meanwhile, efforts to alleviate these challenges are still unknown as some of them (challenges) have been ongoing. Objectives: The objectives of the study were to explore and describe challenges experienced by HCWs when rendering services at a district hospital in Limpopo Province. Methods: The researcher utilised the qualitative explorative approach. The stratified purposive sampling method was utilised to select a sample of 10 participants (nine females and one males), and this was determined by data saturation. Data was collected through semi- structured one-on-one interviews after obtaining ethical clearance from the University Research and Ethics Committee. One central question was posed to participants and probing questions followed with responses that were audio recorded. The six steps as outlined by Braun and Clarke were used to analyse data. Results: The findings yielded two themes and seven subthemes. Participants reported that there was a shortage of resources, leading to poor quality patient care. There was also a lack of support from management and government. Participants indicated that the shortage of resources is a huge stumbling block to provide a holistic and high quality patient care. Shortage of medication was amongst the challenges they face daily. Data was analysed using thematic analysis. Conclusion: Most participants experience similar challenges when rendering services. The challenges are shortage of human resources, resources, equipment and medication as well as poor management support. Therefore, continuous efforts from the government and supporting stakeholders to address these challenges are required
Thesis (MPH.) -- University of Limpopo, 2023
Keywords: Healthcare workers; Poor quality patient care; Shortage of resources; Patient satisfaction; Public hospitals -- Medical staff; Nurses -- Job stress; Health care teams